Design and development of a wall climbing robot and its control system - Akhtaruzzaman, Md.; Samsuddin, Nurul Izzati; Umar, Norsofiana; Rahman , Md Mozasser (2009)
The Robot, named as TRAIN WALL BOT, is designed to navigate on smooth vertical surfaces with the capability to avoid obstacles and overcome if the height is about 1 cm. The design is inspired from train steel wheel movement that contains two actuated legs with rotary motion provided by a DC motor. The Robot uses pneumatic system and the suction force is supplied by an air compressor that turns on intermittently. The suction force ensures the attachment ofthe robot with the wall by using 3 vacuum valves and 6 vacuum pads. The robot is controlled using PIC I6F877A. Two limit switches are used to acknowledge the contact with its navigating surface. Vacuum suction is controlled based on the ON OFF priority ofthe limit switches. Though the design is quiet simple but it is capable to walk, climb vertical smooth surfaces and avoid obstacles. Forward and backward movements are also faster, smoother and more stable (because ofthe coupling design) than other existing wall climbing Robots. In this paper, various aspects of prototype design and development of the Climbing Robot are conveyed including the body, leg, feet design and gait dynamics.